Protección legal de los bienes inmuebles arquitectónicos patrimoniales en el Ecuador que no cuentan con una declaratoria patrimonial - Tapia Tapia, Víctor Mauricio (2015)
The research proposal seeks the answer to a topic that currently has provoked much controversy in the owners of the Real Estate Architectural Heritage which were the subject of a record and inventory, same was the result of work done by the Executive through the different institutions and principal responsibility the National Institute of Cultural Heritage, activity in 2008, after the theft of custody in Riobamba, so the state emergency declared Cultural Patrimony of the Nation, which were channeled resources and a record and inventory nationwide of the different components that form part of the cultural heritage was coordinated. Following the implementation of the inventory are several problems, mainly with architectural heritage assets, as they are the only ones to be considered Cultural Heritage require the making or issuing a declaration that the property belongs to the Cultural Heritage of the Nation and to obtain such declaration is required is a process as a technical report, which involves several steps and the formation of a task force with various professionals such as architects, restorers, historians, archaeologists and engineers; once the respective report done, we proceed to deliver at the National Institute of Cultural Heritage to turn to the Minister of Culture and Heritage requested that the property be declared as part of Cultural Heritage. The dispute between the property owners architectural, and especially the State or the National Institute of Cultural Heritage is responsible and dedicated to protect, maintain and preserve the cultural heritage of the nation entity; this is that it does not exist by the will of the owners retain his patrimonial heritage, since in most cases the raw economic interest and which has caused many homeowners take different actions for the non-conservation of the property assets. With everything said in the previous paragraphs the objective of this research is to provide solutions to the various questions raised by the implementation of such registration and inventory.